CONTESTING FEMALE RELIGIOUS AUTHORITY IN DIGITAL SPACE: A Hermeneutical Study of Reactions to Amina Wadud’s Friday Prayer Leadership - Urbah Rusydiana, Naili Rosa; Lusri Virga, Rika; Afri Muadom, Mohammad (TAJDID: Jurnal Ilmu Ushuluddin, 2025)
This study examines the controversy surrounding female imams in mixed prayers led by Amina Wadud in New York on March 18, 2005, which took place in the digital space. This study does not test the validity of Islamic law regarding female imams, but rather investigates how the practice of female prayer leaders is debated, questioned, defended, and disseminated globally within the realm of religious discourse by various groups, such as academics, religious scholars or authorities, as well as the general public, which is stored in digital archives such as online news portals and digital documents in online libraries. By drawing on a progressive Islamic framework, this research aims to highlight changes in the production of religious meaning and examine the forms of negotiation by spiritual authorities in the public sphere. This research uses a qualitative method with a hermeneutic approach, and it broadly describes two main responses: first, rejection of female imams based on textual interpretations of hadiths and classical fiqh consensus. Second, defense based on a contextual approach to gender justice and reinterpretation of Islamic sources. The analysis in this study is conducted through three aspects: historicization, contextual text production, and public reception. The findings of this study indicate that Wadud's case not only challenges the normative boundaries of religious authority but also opens global discussions about women's spiritual rights and patriarchal structures in religious practices. This practice serves as a valuable starting point in the history of contemporary Islamic discourse, particularly in terms of resistance to masculine interpretations and dominance within religious authority. This study offers a fresh perspective on the legitimacy, interpretation, and transformation of inclusive religious traditions.